Factors associated with respectful maternity care during hospital deliveries: A cross-sectional study in Bangladesh - Fahmida Islam Chowdhury; Moshammat Zebunnessa; Mortuza Begum; Fahmida Shirin; Musarrat Naz; Samira Amir Chowdhury; Hasnatul Jannat; Selina Parvin; Md. Abdur Rafi; Mohammad Jahid Hasan (PLoS ONE, 2025)
Introduction Respectful provision of care is an integral component of quality maternity care service. The objective of the present study was to assess the status of respectful maternity care and its associated factors in public and private hospitals in Bangladesh. Methods A cross-sectional study was conducted at a tertiary care public hospital and a tertiary care private hospital in Chittagong, Bangladesh from October 2023 to September 2024. Face-to-face interviews using a structured questionnaire was conducted to collect data from postnatal women. Respectful maternity care was measured using a validated 15-item tool with four domains (friendly, abuse-free, timely, and discrimination-free care). Logistic regression analysis was used to identify factors associated with respectful maternity care. Results A number of 264 postnatal women from the public hospital and 334 from the private hospital were included in the study. Overall, 55.5% of them received respectful maternity care, with significant differences between public (33.7%) and private (72.8%) hospitals (p-value <0.001). Women in private hospitals reported higher standards across all domains, with the largest disparity in discrimination-free care (98% in private vs. 56% in public hospitals, p < 0.001). Logistic regression showed that women in private hospitals (adjusted odds ratio, aOR 18.10; 95% confidence interval, CI 8.43–42.0), those with facility-level referrals (aOR 2.88; 95% CI 1.59–5.31), and cesarean deliveries (aOR 2.45; 95% CI 1.26–5.07) were significantly more likely to receive respectful maternity care. Conclusion Respectful maternity care was significantly more likely among women delivering in private hospitals, through facility-level referrals, and by cesarean section, indicating gaps in public hospital practices that require attention to ensure respectful care for all mothers.